(untitled) (Biological Sciences - PJSIR, 2025)
Pectin is a natural polysaccharide polymer that has many advantages when used as a coating material. The aim of this study was to assess the effects of pectin based coatings on cucumber quality................................................................the TSS value of uncoated cucumbers increased by 21% at 9th days and 11.6% in pectin based coated cucumbers. In addition, 13.9% the reduction in hardness was observed in uncoated cucumbers when compared to 7% in pectin-coated cucumbers. Pectin based coatings extend the shelf life, enhance preservation and improve appearance.